Dismissing class - Cotal San Martin Vladimir (Nordicom Review)
Neoliberal globalisation has expanded transnational corporations’ (TNCs) boundaries of operation and sphere of exploitation, particularly in the Global South where much of the production of traditional TNC manufacturing now occurs. In this article, using a longitudinal approach, I conduct a detailed critical discourse analysis of a large Swedish press corpus reporting on TNC activities in Global South countries. The analysis suggests that the issue of workers’ conditions is made relevant to the Swedish public through a “consumer framework” that not only confers proximity and relevance on the topic, but also effectively recontextualises agency and responsibility towards particular or individual social actors, obscuring the class dimension of labour relations and global production. Moreover, rooted in a highly problematic colonial imagery, exploitation in the Global South is seen as a “cultural problem” of “them” rather than a problem related to the social and spatial relations of global capitalism.